Chorioamnionitis: clinical, anamnestic and molecular-genetic parallels - I. V. Ignatko; A. D. Megrabyan; V. M. Anokhina; A. A. Churganova; T. V. Rasskazova; O. V. Zavyalov; V. A. Titov; V. O. Petrova (Акушерство, гинекология и репродукция)
Aim: to determine clinical, anamnestic and molecular-genetic parallels in emergence of clinical chorioamnionitis (CA) and severe forms of intrauterine infections (IUI) in high-risk pregnant women.Materials and Methods. A single-center prospective cohort comparative case-control study was conducted by examining 58 pregnant female patients aged 18 to 42 years with a verified CA diagnosis during pregnancy and childbirth at different gestation stages (main group), and 35 age-matched pregnant women with uncomplicated pregnancy and no significant extragenital pathology, aggravated factors of obstetric and gynecological history and risk factors for developing CA (control group), observed and performed a delivery in Yudin City Clinical Hospital. All women underwent clinical, anamnestic, laboratory, instrumental and molecular-genetic examitation. We studied the polymorphism of genes FCGR2A (Fc fragment of immunoglobulin G receptor IIa), IFN-γ (interferon gamma), IL-10 (interleukin-10), IL-6 (interleukin-6) and MBL2 (mannose binding lectin 2) to determine their role in assessing a risk of maternal and neonatal infection.Results. Among the patients with developed clinical CA vs. control subjects, more of them had a history of abortion and miscarriages (17.24 %), comorbid with chronic arterial hypertension (13.79 %), previous surgical interventions (27.59 %), as well as chronic inflammatory diseases (chronic tonsillitis, bronchitis, pyelonephritis, sinusitis; 27.59 % vs. 17.14 %). In addition to risk factors directly related to the infectious and inflammatory unfavorable background, they also had a significantly higher rate of obstetric complications: moderate preeclampsia - 6 (10.34 %) cases, threat of miscarriage or premature birth - 14 (24.14 %) cases vs. 1 (2.86 %) case in control group (p = 0.007), polyhydramnions - 4 (6.9 %) cases, placental insufficiency - 6 (10.34 %) cases. The frequency of premature rupture of membranes was 31.03 % in women with CA. Questionable cardiotocography (CTG) type was found in 24 (41.38 %) women with CA vs. 4 (11.4 3%) women without CA (p = 0.003), the pathological CTG type was observed only in women with CA. In the group with clinical CA and neonatal IUI, the combination of genotypes AG rs1801274 FCGR2A, TT rs2430561 (IFN-γ)+874, GC rs1800795 (IL-6)-174 occurs in 80.65 % (25/31), whereas in women without severe neonatal IUI - in 37.04 % (10/27) (odds ratio (OR) = 7.08; 95 % confidence interval (CI) = 2.166-23.166). In addition, the combination of alleles TT rs2430561 (IFN-γ)+874, GC+CC rs1800795 (IL-6)-174, AA rs1800450 MBL2 codon 54 was detected in 90.32 % (28/31) vs. 44.44 % (12/27) in main and control group (OR = 11.667; 95 % CI = 2.842-47.886), respectively.Conclusion. The study data evidence about importance of identifying genes for developing CA and neonatal septic complications to optimize and personalize management of high-risk patients (premature birth, infections during pregnancy, premature rupture of membranes).